Study of the effect of incubation periods and the source of carbon and nitrogen in the growth of the fungus Aureobasidium pullulans and the production of gluconic acid - Mohammad Basheer Ismael Kasim; Rawaa Mohammad Jarjees; AbdulKareem Sulayman Hasan (College of Education for Pure Sciences, 2013)
ABSTRACT In this study (16) different local isolates of the yeast like fungus Aureobasidium pullulans were obtained. These isolates were isolated from uninfected leaves of many wild and cultured plants. These isolates were identified as real isolates of A.pullulans depending on the microscopic examination to determine the polymorphic form of this fungus. These isolates were screened regarding their efficiency to produce gluconic acid. Two isolates only, A.pullulans MU1 and A.pullulans MU2 showed a high ability to produce gluconic acid. The two isolates were tested to produce gluconic acid in the liquid media. A.pullulans MU1 showed a high ability to produce gluconic acid after three days of incubation and therefore this isolate was selected in the latter experiments. In order to enhance the ability of the isolate to produce the acid we study the effect of the medium culture components from carbon and nitrogen source on the production. The results showed that best carbon source to produce maximum quantity of the acid was sucrose at the concentration of 15% so gave (15.1) g/L and best nitrogen source was ammonium chloride at the concentration of (4.8) g/L so gave (25.45) g/L of gluconic acid.